Poverty and nutrition in Bolivia - World Bank (Washington, D.C.: World Bank, 2002)
This publication commissioned reviews of the available information on Bolivia water and sanitation, sustainable livelihoods, nutrition program evaluations and nutrition institutions.
Includes bibliographical references
osa;1/9/2016
Loans
Keywords: Poverty; Poverty - Bolivia; Nutrition - Bolivia; Public health - Bolivia; Mslnutrition - Bolivia